Pelatihan Pembuatan Media Pembelajaran Edukatif di Sekolah Dasar Inpres Werwaru - Lestari Lestari; Ince Wattimury; Sefanya Sairiltiata (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
One of the educational learning media uses a smart board. This media is one of the learning media that can be used by teachers in carrying out learning in the classroom. This media is an innovative media in the world of education so that training is needed for teachers to be able to create and apply it to learning materials in schools. This community service aims to improve the skills and creativity of elementary school teachers in teaching through training in making educational media. This media is effective in attracting interest and facilitating students' understanding of the subject matter, this community service program is expected to facilitate more interactive and interesting learning. This training consists of delivering material related to educational learning media, training in making learning media and questions and answers. This activity was carried out on July 20, 2024 at SD Inpres Werwaru. The results of this activity are increased understanding of the material, increased skills in making creative media, and skills in using learning media. The evaluation results show that training in making educational learning media can improve understanding of the material, skills in making creative media, and skills in using learning media.